(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Acquiring English Language skills in traditional Classroom is very difficult for students, particularly who study English as a second language(ESL).Hence the ideal way to learn these skills effectively is to adopt Blended Learning which employs a mix of ‘face-to-face’ and ‘online learning’. In this age of Information and Communication Technology where high speed data and number of learning tools and apps are available, Blended Learning approach helps the students in learning these skills and honing them continuously. Blended Learning also removes boundaries for learning and offers virtual libraries and schools without walls (Askar, 2003 Halis, 2001). In Blended Learning, there is a scope for ‘self-learning’ which will do a major good for the learner by shedding his fears and inhibitions and help him learn at his own pace. It also provides scope for students to get inspired while watching the videos of effective communication offered by experts. Overall, Blended Learning is a trenchant method to equip ESL students with skills needed for life in the 21st century.